Parental psychopathology and the risk of suicidal behavior in their offspring: results from the world mental health surveys (2011)
Previous research suggests that parental psychopathology predicts suicidal behavior among offspring; however, the more fine-grained associations between specific parental disorders and distinct stages of the pathway to suicide are not well understood. We set out to test the hypothesis that parental disorders associated with negative mood would predict offspring suicide ideation, whereas disorders characterized by impulsive aggression (for example, antisocial personality) and anxiety/agitation (for example, panic disorder) would predict which offspring act on their suicide ideation and make a suicide attempt. Data were collected during face-to-face interviews conducted on nationally representative samples (N= 55 299; age 18þ) from 21 countries around the world. We tested the associations between a range of parental disorders and the onset and persistence over time (that is, time since most recent episode controlling for age of onset and time since onset) of subsequent suicidal behavior (suicide ideation, plans and attempts) among offspring. Analyses tested bivariate and multivariate associations between each parental disorder and distinct forms of suicidal behavior. Results revealed that each parental disorder examined increased the risk of suicide ideation among offspring, parental generalized anxiety and depression emerged as the only predictors of the onset and persistence (respectively) of suicide plans among offspring with ideation, whereas parental antisocial personality and anxiety disorders emerged as the only predictors of the onset and persistence of suicide attempts among ideators. A dose-response relation between parental disorders and respondent risk of suicide ideation and attempt was also found. Parental death by suicide was a particularly strong predictor of persistence of suicide attempts among offspring. These associations remained significant after controlling for comorbidity of parental disorders and for the presence of mental disorders among offspring. These findings should inform future explorations of the mechanisms of intergenerational transmission of suicidal behavior.